Identification of Autism Disorder Spectrum Based on Facial Expressions - Mahsa Naeeni Davarani; Touraj Bnirostam; Hayedeh Saberi (Ital Publication, 2017)
The study of emotions has always been a matter for philosophers and psychologists. The purpose of this research is to identify and categorize children with autism disorder using diagnosis of the faces emotion in eight states (neutral, anger, ridicule, hate, fear, happiness, sadness and wonder). The method of this research is descriptive-analytic. To collect samples from 80 children with autism disorder, we take images in each of the 8 cases. MATLAB software has been used to analyse photos accurately. The results show that children who are in first group according to DSM-5, they have at least six mode of the listed eight modes. Children who are in the second category of DSM-5, they experience between three to five feelings. It is also observed that children who are in the third category according to DSM-5, can experience only one to two feelings.